PENGARUH PEMBERIAN BEBERAPA DOSIS PUPUK ORGANIK CAIR CROCOBER PLUS TERHADAP PERTUMBUHAN TANAMAN KAYU MANIS (Cinnamomum burmanni Ness ex) - Yusnaweti Yusnaweti; Yustitia Akbar (Jurnal Pertanian UMSB: Penelitian dan Kajian Ilmiah Bidang Pertanian, 2018)
Research on influence the allotment of some doses fertilizer liquid OrganicCrocober Plus on The Growth of The Kayu manis Plant (Cinnamomum burmanni Ness ex) To the provision of a couple doses fertilizer liquid Organic Crocober Plus carried out in the half shadows and laboratory the faculty Agricultural Muhammadiyah University West Sumatera. Research purposes, to get a dose of fertilizer complex the organ which is proper for Kayu manis plants . Design used is Random Complete ( RAL ), with 4 the economic situation and 4 remedial: doses fertilizer the liquid Organic Crocober Plus 0, 5, 10 and 15 ml /l. Data observation dianalis in statistika by test f the first real 5 percent . The results of reasarch show to the growth of plants Kayu manis doses 15 l /ml plants give the best results to the growth of plants Kayu manis.Key words : Crocober Plus and Kayu manis